Prevalence of malnutrition and its association with activities of daily living in older adults attending primary health care centers: a multistage cross-sectional study: A multistage cross-sectional study - Alhamdan, Adel A.; Bindawas, Saad M.; Alshammari, Sulaiman A.; Al-Amoud, Maysoon M.; Al-Orf, Saada M.; Al-Muammar, May N.; Calder, Philip C. (Progress in Nutrition, 2019)
Objective: Nutritional status plays a vital role in the quality of health of older adults. Thus, we aim to assess nutritional status and its association with functional status in older adults. Methods: A cross-sectional descriptive study with a multistage stratified sampling strategy was carried out in primary health care centers (PHCCs). Community-dwelling older adults ≥ 60 years of age (n=2045) participated in the study. Nutritional status was assessed using the mini-nutritional assessment tool, and BMI was measured. Functional status was measured by Katz index of independence in activities of daily living (ADL) and its relationship to nutritional status was examined and assessed using chi-square test and binary logistic regression. Results: Obesity prevalence was high (43.2%) while 20.9% were classified as at risk of malnutrition or were malnourished. There was a significant association between nutritional status and ADL. Conclusions: Assessing nutritional status of older adults identified a high prevalence of both undernutrition and obesity. Such assessments should be routine practice in PHCCs.